Structural engineering for professional engineers' examinations : Including statics, mechanics of materials and civil engineering - Kurtz, Max (New York : McGraw Hill Education, 1978)
This book helps the reader prepare for the P.E. examinations by presenting a vast array of problems that are characteristics of these examinations.
1. Analysis of force systems -- 2. Geometrical properties of an area -- 3. Analysis of stress and strain -- 4. Pressure vessels - riveted and welded connections -- 5. Stresses in beams -- 6. Design of steel beams and plate girders -- 7. Deflection of beams - statically indeterminate beams -- 8. Torsion -- 9. Steel members in tension and compression -- 10. Trusses -- 11. Timber design -- 12. Loads on foundations - stability of structures -- 13. Properties of concrete columns.
Includes index.
Keywords: STRUCTURAL ENGINEERING